Bortezomib‐containing induction regimens in transplant‐eligible myeloma patients: A meta‐analysis of phase 3 randomized clinical trials. Issue 23 (4th September 2013) - Nooka, Ajay K.; Kaufman, Jonathan L.; Behera, Madhusmita; Langston, Amelia; Waller, Edmund K.; Flowers, Christopher R.; Gleason, Charise; Boise, Lawrence H.; Lonial, Sagar
Abstract : BACKGROUND: The objective of this meta‐analysis in patients with myeloma was to test the hypothesis that the addition of bortezomib to induction therapy not only improves the depth of response but also improves post‐transplant progression‐free survival (PFS) and overall survival (OS) outcomes. METHODS: Phase 3 trials that randomized newly diagnosed, transplant‐eligible patients with myeloma to receive either a bortezomib‐containing induction regimen (BCIR) or a nonbortezomib‐containing induction regimen (NBCIR) were identified. Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines were adapted for data synthesis, and comprehensive meta‐analysis software was used to report pooled data as hazard ratios or odds ratios under a random‐effects model. RESULTS: Four published phase 3 trials that included 2169 patients were analyzed. The postinduction and post‐transplant pooled odds ratio for achieving a complete response/near complete response or a very good partial response or better and the overall response rate were higher with BCIR. The pooled hazard ratios for 3‐year PFS and OS were 0.71 (95% confidence interval, 0.60‐0.83; P  < .00, 001) and 0.79 (95% confidence interval, 0.66‐0.96; P  = .014), respectively, favoring BCIR. The odds of developing selected grade ≥3 toxicities (peripheral neuropathy and varicella‐zoster virus reactivation) also were higher with BCIR. CONCLUSIONS: The current meta‐analysis demonstrated that BCIR results in an improved depth of response, which translates into improved post‐transplant PFS and OS outcomes despite a higher incidence of toxicity. This analysis supports the concept that the choice of induction regimen can influence post‐transplant outcomes such as PFS and OS. Cancer 2013 ;119:4119–4128. © 2013 American Cancer Society . Abstract : The receipt of bortezomib‐based induction therapy in a meta‐analysis of patients with myeloma demonstrates improvement in the depth of response before and after transplant. Bortezomib‐based induction is associated with a higher incidence of adverse events but also with improved progression‐free and overall survival after transplant.